Kajian kelebihan menggunakan ilustrasi sebagai bahasa visual dalam memahami UKBS 1984 - Ahmad Firkry Khairy Ahmad Mustafa; Suhana Johar; Mohd Khairul Azhar Mat Sulaiman (Penerbit Universiti Kebangsaan Malaysia, 2023)
The use of the Uniform Building By-Laws 1984 (UBBL) is no stranger among architectural practitioners and to the Local Authorities (PBT) in general, in which the UBBL also has several different versions according to PBT in each state. UBBL is a ‘must book’ in every local municipal office and in the architectural firms including to the architectural students in Malaysia. This showed how important the UBBL, however, there is a difficulty in understanding the content stated among the students and practitioners of the industry. Among the factors that make it difficult to understand is due to the use of legal language in which the UBBL is a law that has been subsidized under Act 133 on 05 June 1974. In addition, the absence of a simple and concise explanation for each clause in the UBBL and the absence of illustrations or diagrams that could explaining a clause. The use of illustrations as a visual language can help to ease understanding for students and the architecture industry of the meanings, principles, procedures and anything relates to subject matters. This paper is to discuss the meaning of visual or illustrative language, its history, the importance, and the impact of its usage in other fields. The methodology is through the analysis of relevant secondary sources. The findings showed the type of illustration that is fits to be used is the industry and technical illustration as they can explain the meaning of a clause in UBBL by using simple elements such as lines, geometries, scales and the stated measurements. All these features are common in the field of architecture, thus facilitating the process of understanding UBBL within a short time among the architectural students and practitioners.